Cerebral White Matter Disruption in Creutzfeldt-Jakob Disease - Lee, H.; Cohen, O.S.; Rosenmann, H.; Hoffmann, C.; Kingsley, P.B.; Korczyn, A.D.; Chapman, J.; Prohovnik, I. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Human prion diseases are known to cause gray matter degeneration in specific cerebral structures, but evidence for white matter involvement is scarce. We used DTI to test the hypothesis that white matter integrity is disrupted in human CJD during the early stages of the disease. MATERIALS AND METHODS: Twenty-one patients with the E200K variant of CJD and 19 controls participated in DTI studies conducted on a 1.5T MR imaging scanner. The data were quantitatively analyzed and mapped with a voxelwise TBSS method. RESULTS: We found significant reductions of FA in patients with CJD in distinct and functionally relevant white matter pathways, including the corticospinal tract, internal capsule, external capsule, fornix, and posterior thalamic radiation. Moreover, these FA deficits increased with disease duration, and were mainly determined by increase of radial diffusivity, suggesting elevated permeability of axonal membranes. CONCLUSIONS: The findings suggest that some of the symptoms of CJD may be caused by a functional dysconnection syndrome, and that the leukoencephalopathy is progressive and detectable fairly early in the course of the disease. ADaxial diffusivityCJDCreutzfeldt-Jakob diseaseFAfractional anisotropyMDmean diffusivityMMSEMini-Mental State ExaminationRDradial diffusivityTBSStract-based spatial statistics